Polydomy in the ant Ectatomma opaciventre - Tofoloa, Viviane C. [UNESP]; Giannotti, Edilberto [UNESP]; Neves, Erika F.; Andrade, Luis H. C.; Lima, Sandro M.; Suarez, Yzel R.; Antonialli-Junior, William F. (Univ Arizona, 2014)
Tropical ants commonly exhibit a hyper-dispersed pattern of spatial distribution of nests. In polydomous species, nests may be satellites, that is, secondary structures of the main nest, where the queen is found. In order to evaluate whether the ant Ectatomma opaciventre Roger (Formicidae: Ectatomminae) uses the strategy of building polydomous nests, the spatial distribution pattern of 33 nests in a 1,800 m(2) degraded area located in Rio Claro, SP, Brazil, were investigated using the nearest neighbor method. To complement the results of this investigation, the cuticular chemical profile of eight colonies was analyzed using Fourier transform infrared photoacoustic spectroscopy (FTIR-PAS). The nests of E. opaciventre presented a hyper-dispersed or regular distribution, which is the most common in ants. The analysis of the cuticular hydrocarbons apparently confirmed the hypothesis that this species is polydomous, since the chemical profiles of all studied colonies with nests at different sites were very similar to the chemical signature of the single found queen and were also different from those of colonies used as control.
Keywords: colony organization; cuticular hydrocarbons; nestmate recognition; satellite nests; spatial distribution